THE ABUNDANCE AND DIVERSITY OF THRIPS (THYSANOPTERA: THRIPIDAE) ON CHILI (CAPSICUM ANNUUM L.) AND CAYENNE (CAPSICUM FRUTESCENS L.) IN BOGOR - Hutasoit, Rudi Tomson; Triwidodo, Hermanu; Anwar, Rully (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2019)
The Abundance and Diversity of Thrips (Thysanoptera: Thripidae) on Chili (Capsicum annuum L.) and Cayenne (Capsicum frutescens L.) in Bogor. This research aimed to study the abundance and diversity of thrips on chili pepper and cayenne pepper plants. Observation of thrips was conducted on chili pepper and cayenne pepper in fourteen sites in four different locations in Bogor that are: Dramaga, Cibungbulang, Tenjolaya, and Cisarua. Thrips were collected from leaves and flowers from 10 plant samples that had been selected randomly. The thrips were identified and the number of thrips were calculated. The abundance of adults, nymphs, and total of thrips on the flowers of chili pepper was 0.39, 0.01, and 0.40 thrips/flower respectively. Meanwhile, the abundance of adults, nymphs, and total of thrips on the flowers of cayenne pepper was 0.36, 0.02, and 0.38 thrips/flower respectively. The abundance of adults, nymphs, and total of thrips on the leaves of chili pepper was 0.68, 0.12, and 0.81 thrips/twiq respectively. Meanwhile, the abundance of adults, nymphs, and total of thrips on the leaves of cayenne pepper was 0.47, 0.14, and 0.61 thrips/twiq respectively. Four species of thrips were found infesting flowers of chili pepper and cayenne pepper i. e. Thrips parvispinus, T. hawaiiensis, Scirtothrips dorsalis, and Haplothrips gowdeyi.  Species of T. parvispinus, T. hawaiiensis, S. dorsalis belong to suborder of Terebrantia family Thripidae, meanwhile H. gowdeyi belongs to suborder Tubulifera family Phlaeothripidae. T. parvispinus is the most dominant species found infesting flowers and leaves of the chilli pepper and cayenne pepper were 71% and 56 %.